Information and Participation in Social Programs - Coady, David; Martinelli, César; Parker, Susan W. (Oxford University Press on behalf of the World Bank, 2014)
Participation in social programs, such as clubs and other social organizations, results from a process in which an agent learns about the requirements, benefits, and likelihood of acceptance related to a program, applies to be a participant, and, finally, is accepted or rejected. We propose a model of this participation process and provide an application of the model using data from a social program in Mexico. Our empirical analysis illustrates that decisions at each stage of the process are responsive to expectations about the decisions and outcomes at the subsequent stages and that knowledge about the program can have a significant impact on participation outcomes.